The Effect of Social Media Promotion and Word of Mouth on Purchase Decisions at Humaloka Coffee in Bandung City - Reza Ferdiansyah; Putut Raka Santoso (Takaza Innovatix Labs Ltd., 2026)
Bandung's coffee shop boom heightens MSME competition like Humaloka Coffee, depending on social media promotion and word-of-mouth in digital trends. This study analyzes their effects on purchase decisions via quantitative descriptive-verification survey of 96 non-probability samples from December 2025 visitors, using online questionnaires, observation, interviews, multiple linear regression, classical tests, and SPSS. Results reveal